Air-to-land transitions: from wingless animals and plant seeds to shuttlecocks and bio-inspired robots - Ortega-Jimenez, Victor M.; Jusufi, Ardian; Brown, Christian E.; Zeng, Yu; Kumar, Sunny; Siddall, Robert; Kim, Baekgyeom; Challita, Elio J.; Pavlik, Zoe; Priess, Meredith; Umhofer, Thomas; Koh, Je Sung; et al. (Bioinspiration and Biomimetics, 2023)
Recent observations of wingless animals, including jumping nematodes, springtails, insects, and wingless vertebrates like geckos, snakes, and salamanders, have shown that their adaptations and body morphing are essential for rapid self-righting and controlled landing. These skills can reduce the risk of physical damage during collision, minimize recoil during landing, and allow for a quick escape response to minimize predation risk. The size, mass distribution, and speed of an animal determine its self-righting method, with larger animals depending on the conservation of angular momentum and smaller animals primarily using aerodynamic forces. Many animals falling through the air, from nematodes to salamanders, adopt a skydiving posture while descending. Similarly, plant seeds such as dandelions and samaras are able to turn upright in mid-air using aerodynamic forces and produce high decelerations. These aerial capabilities allow for a wide dispersal range, low-impact collisions, and effective landing and settling. Recently, small robots that can right themselves for controlled landings have been designed based on principles of aerial maneuvering in animals. Further research into the effects of unsteady flows on self-righting and landing in small arthropods, particularly those exhibiting explosive catapulting, could reveal how morphological features, flow dynamics, and physical mechanisms contribute to effective mid-air control. More broadly, studying apterygote (wingless insects) landing could also provide insight into the origin of insect flight. These research efforts have the potential to lead to the bio-inspired design of aerial micro-vehicles, sports projectiles, parachutes, and impulsive robots that can land upright in unsteady flow conditions.
Keywords: Aerial righting; Aerodynamic forces; Bio-inspired robots; Morphing; Physical damages; Plant seeds; Predation risk; Samara; Self-righting; Wingless animal; Animals; Biomechanical Phenomena; Flight, Animal; Gravitation; Insecta; Robotics; Seeds; aerial righting; bio-inspired robots; landing; samaras; wingless animals